Association of glucose homeostasis measures and metabolic syndrome with knee cartilage defects and cartilage volume in young adults - Meng, T; Venn, A; Cicuttini, F; March, L; Dwyer, T; Cross, M; Laslett, L; Jones, G; Antony, B; Ding, C (Elsevier, 2019)
Purpose: To describe the associations of glucose homeostasis measures and metabolic syndrome (MetS) measures with knee cartilage defects and cartilage volume in young adults.